Objetos virtuales de aprendizaje como mediación didáctica para el desarrollo del pensamiento matemático en los estudiantes de la Básica Primaria (2021)
The purpose of this research was to analyze the contribution of Virtual Learning Objects as a didactic mediation to the development of mathematical thinking in elementary school students, it was structured under the complementary emerging paradigm; a mixed descriptive-explanatory research approach and a pre-experimental research design, with a single group of 24 students from grade 5, of the I.E. Nuestra Señora de la Asunción de Fresno-Tolima, to whom a questionnaire is applied in order to identify the needs and expectations regarding the use of ICT during a process of teaching and learning mathematics; a pre-test test to diagnose the level of mathematical thoughts, from which an offline OVA was designed and applied, and finally, a standardized post-test was applied and whose results were compared with the results obtained in the pre-test, it was demonstrated that the students developed mathematical thinking, with an increase in the components: numerical-variational from 41% to 55%; random from 48% to 62% and metric-geometric from 36% to 55%; while mathematical competencies: reasoning from 38% to 58%, communication 42% to 56% and problem solving from 42% to 61%. It is concluded that the inclusion of OVAs as a didactic mediation contributes to the development of mathematical thinking, enabling the strengthening of components and competencies.